Assessing 16 Fundamental Motives With Fewer Than 50 Items: Development and Validation of the German 16 Motives Research Scales (16mrs) - Dörendahl, Jan; Greiff, Samuel; Niepel, Christoph (Frontiers in Psychology, 2021)
Psychometrically sound short scales are required to comprehensively yet economically assess fundamental motives in research settings such as large-scale assessments. In order to provide such a time- and cost-efficient instrument, we conducted three studies (N = 1,568) to select and validate 16 German scales with three items each assessing fundamental motives (16 motives research scales; 16mrs). In Study 1, we applied a top-down construction process to develop a preliminary item pool on the basis of a thorough revision of existing construct definitions. In Study 2, we chose an approach that allowed us to balance the optimization of psychometric properties with content coverage to select three-item scales for each of the 16 motives. For the item selection process, we combined exploratory factor analyses, confirmatory factor analyses, ant colony optimization algorithm, and Mokken scale analyses. In Study 3, we cross-validated the results obtained in Study 2 and placed the 16mrs in a nomological network consisting of Big Five traits and Power, Achievement, Affiliation, Intimacy, and Fear motives. The results of these studies indicate that the 16mrs can be used to reliably and validly assess fundamental motives that represent a level of personality that differs from the Big Five and covers motivational aspects beyond the well-established Power, Achievement, Affiliation, Intimacy, and Fear motives. Limitations concerning the reliability of the Autonomy scale and the empirical discrimination of the Dominance and Status scales are discussed. In addition to the validated German version, we also provide the English translation of the items, which, however, need to be validated before use.